The impact of public performance reporting on cancer elective surgery waiting times: a data linkage study - Khic-Houy Prang; Rachel Canaway; Marie Bismark; David Dunt; Julie A. Miller; Margaret Kelaher (BMC, 2021)
Abstract Background Excessive waiting times for cancer elective surgery are a concern in publicly funded healthcare systems. Several countries including Australia have introduced healthcare reforms involving time-based targets and public performance reporting (PPR) of hospital data. However, there is mixed evidence of their benefits. We sought to examine the impact of targets and PPR of cancer elective surgery waiting times on access to breast, bowel and lung cancer elective surgery. Methods We analysed routinely-collected linked data on admissions and waiting times for patients aged 15 years or over (n = 199,885) who underwent cancer surgery in a public hospital in Victoria, Australia over a 10-year period. We conducted difference-in-differences analyses to compare waiting times before (2006-07 to 2011-12) and after (2012-13 to 2015-16) the introduction of PPR in meeting these targets. Results Across all cancer types, urgent patients were all treated within 30 days before and after PPR. Following PPR, there was a slight increase in the mean waiting times across all cancer types and urgency categories. Patients with lung cancer waited on average two and half days longer for treatment and patients with breast cancer waited on average half-a-day less. There was no effect of PPR on waiting times for patients with bowel cancer across urgency categories. Conclusions Our findings suggest that time-based targets and PPR had minimal impact on surgical waiting times. This may be due to reasonable waiting times prior to PPR, improved efficiency being masked by 20% growth in the population, lack of public knowledge that waiting times are publicly reported, or lack of real-time reporting to drive behavioural change. The use of generic elective surgery recommended waiting time measures for cancer is discussed.